Предмет: Алгебра,
автор: kykypyzkanumberone
При каком значении Х выражение
6,2x - 9 - (-2,8x + (6 - 1,3x) - 12,84) равно 0 ?
Ответы
Автор ответа:
1
6,2x - 9 - (- 2,8x + (6 - 1,3x) - 12,84) = 0
6,2x - 9 - (- 2,8x + 6 - 1,3x - 12,84) = 0
6,2x - 9 - (- 4,1x - 6,84) = 0
6,2x - 9 + 4,1x + 6,84 = 0
10,3x = 2,16
x = 108/515
Похожие вопросы
Предмет: Другие предметы,
автор: nglushko2012
Предмет: Русский язык,
автор: mashgoryaeva
Предмет: Другие предметы,
автор: nglushko2012
Предмет: Алгебра,
автор: charusovamasha
Предмет: ОБЖ,
автор: 13Света13